The Influence of the Treffinger Model on Critical Thinking Skills in Indonesian History Subjects: - - Aulia Meylita; Arif Permana Putra; Ana Nurhasanah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to determine the effect of Treffinger learning on critical thinking skills, subject of Indonesian history class X at MAN 4 Pandeglang. Method used is quantitative quasi-experimental type using nonequivalent control group design. The study took from May to October 2024. Hypothesis two-party t-test with the independent sample t-test, the t-test value obtained was 4.05 ≠ t-table of 1.66 with significance level 0.05. Statistical